Evaluasi Kinerja Manajemen Konstruksi Proyek Pembangunan Kantor Dinas Kesehatan - Ruly Frans Albar; Ganjar Jojon Johari (Jurnal Konstruksi, 2023)
Construction Management can be in the form of a business entity in which human resources are needed who are experts in their respective fields which include POAC (Planning/Planning, Organizing/Organizing, Actuating/Implementing, and Controlling/Supervision). The Garut District Health Office Development Project was built to improve the quality of the office and improve the quality of public services. In the implementation of a project, of course it cannot be avoided from various problems that slowly arise. This is a serious challenge, how will the construction management itself try to solve various problems that occur so that it can proceed according to the initial plan. This study aims to find out what factors influence the performance of construction management in and to find out the actions taken to overcome the problems that occur so that the implementation of construction management can run well. The method used in this research is ranking analysis method. This study involved consultants and contractors to fill out a questionnaire. There are 30 respondents in this study. The results of this study are that the factors that influence the construction management work system are mostly in the supervision or controlling process, which obtains an average value of 3.56. To control the factors that affect the construction management work system in the control process, you can analyze the constraints that occur in the field and then catch up on delays in progress that occur quickly and precisely.